Modification of copper surfaces with cathodic arc aluminum plasma - Çorlu, Beril; Ürgen, Mustafa (Elsevier BV, 2010)
Abstract In the present study, surfaces of copper substrates were modified with aluminum plasma using cathodic vacuum arc (CVA) physical vapor deposition based technique. Surface treatments were carried out as a function of bias voltage for various time intervals. The effect of long and short durations of ion bombardment on the resulting microstructural features of the treated surfaces were studied and discussed. It was observed that surface alloying and diffusion processes were enhanced by the application of the ion bombardment and thick (10–15 μm) modified zones were achieved in a relatively short processing time (15–20 min). In the experiment executed with long bombardment duration, the modified zone consisted of a mixture of martensitic β 1 -AlCu 3 phase and (Cu) solid solution, accompanied with a minor amount of γ 1 -Al 4 Cu 9 intermetallic phase, whereas, in the experiment involving short total bombardment duration, the modified surface predominantly consisted γ 1 -Al 4 Cu 9 intermetallic phase, accompanied with martensitic β 1 -AlCu 3 phase at the copper aluminum interface.